Peningkatan Hasil Belajar Siswa Pada Pembelajaran IPS melalui Penerapan Model Project Based Learning - Sunardin, Sunardin (Universitas Negeri Makassar, 2018)
This research is a descriptive qualitative study that uses a class action research design. This study aims to improve student learning outcomes in social studies learning through the application of project based learning models. Classroom action research is carried out in two cycles consisting of four stages of implementation, namely planning, action, observation, and reflection. Data collection techniques were carried out through written tests at the end of each cycle by using multiple choice instruments. The results showed there was an increase in student learning outcomes in social studies learning from cycle I to cycle II with a percentage increase in student learning outcomes 85% of the 20 students had reached the minimum standard of completeness. The increase in student learning outcomes occurs because of increasing students' skills in solving problems when the project based learning model is applied to the implementation of learning activities